Diagnostic value of an increase in central venous pressure during SBT for prediction of weaning failure in mechanically ventilated patients: A cross‐sectional study. Issue 4 (13th April 2023) - Ghamari, Ali Akbar; Amini, Keivan; Daei Sorkhabi, Amin; Sarkesh, Aila; Saghaleini, Seyed Hadi; Asghari, Roghayeh; Rezayi, Mansour; Mahmoodpoor, Ata
Abstract: Background: Timely and successful extubation is an essential step forward in clinical practice to minimize complications of mechanical ventilation and unsuccessful weaning processes. Thus, research into predictive factors of weaning outcome to optimize spontaneous breathing trial (SBT) precision before extubation is critical in intensive care practices. In this study, we aimed to investigate the predictive factors of the weaning outcome before and during SBT in mechanically ventilated patients. Methods: In this cross‐sectional study, 159 mechanically ventilated patients who were eligible for SBT were enrolled. Of these patients, 140 had successful extubation, whereas the remainder failed. Each patient's PaCO2 and PaO2 levels, respiratory rate (RR), SpO2, mean arterial pressure (MAP), heart rate (HR), and central venous pressure (CVP) values at the start of SBT, 3 min later, and at the end of SBT were measured. These values, along with the patients' clinical characteristics, were then investigated to determine if there was any correlation between these variables and the weaning outcome. Results: Our analysis revealed that increase in CVP, independent of hemoglobin (Hb) concentration, PaO2, SpO2, duration of mechanical ventilation (MV), length of intensive care unit (ICU) stay, and SBT process, as well as underlying disease, was positively correlated with extubation/weaning failure. While age, gender, vital signs (MAP, RR, and HR), sequential organ failure assessment (SOFA), and acute physiology and chronic health evaluation (APACHE) scores had no significant correlation with patients' extubation outcomes. Conclusion: According to our findings, integrating CVP assessment into SBT besides routine indices measurement and monitoring can be considered for the prediction of weaning outcome in critically ill mechanically ventilated patients.